Development and Usability Evaluation of an Interactive Digital Literacy E-Module Based on Mayer’s Multimedia Learning Principles for Phase E Students - Dwi Irawati Nur Aini; Rizki Hikmawan (FKIP - Universitas Riau, 2026)
High school students still face difficulties in distinguishing factual information from hoaxes in digital media, indicating the need for interactive learning media that can strengthen digital literacy skills. This study aimed to develop an interactive digital literacy e-module based on Mayer’s multimedia learning principles and evaluate its usability using the System Usability Scale (SUS). The study employed a Design and Development Research (DDR) approach consisting of needs analysis, design, development, and evaluation stages. The e-module materials were designed using Canva by integrating text, images, and videos, while interactive questions and instant score feedback were provided through Google Sites. The usability evaluation involved 24 Phase E students who used the e-module during informatics learning activities. The results showed an average SUS score of 82.08, which falls into the Acceptable category, Grade A, and Excellent adjective rating. These findings indicate that the e-module was easy to use, comfortable, and well accepted by students. Therefore, the developed e-module can be considered a usable and appropriate learning medium to support digital literacy learning, particularly in helping students critically evaluate the accuracy of information.